A roadmap for global synthesis of the plant tree of life. Issue 3 (30th March 2018) - Eiserhardt, Wolf L.; Antonelli, Alexandre; Bennett, Dominic J.; Botigué, Laura R.; Burleigh, J. Gordon; Dodsworth, Steven; Enquist, Brian J.; Forest, Félix; Kim, Jan T.; Kozlov, Alexey M.; Leitch, Ilia J.; Maitner, Brian S.; et al.
Abstract: Providing science and society with an integrated, up‐to‐date, high quality, open, reproducible and sustainable plant tree of life would be a huge service that is now coming within reach. However, synthesizing the growing body of DNA sequence data in the public domain and disseminating the trees to a diverse audience are often not straightforward due to numerous informatics barriers. While big synthetic plant phylogenies are being built, they remain static and become quickly outdated as new data are published and tree‐building methods improve. Moreover, the body of existing phylogenetic evidence is hard to navigate and access for non‐experts. We propose that our community of botanists, tree builders, and informaticians should converge on a modular framework for data integration and phylogenetic analysis, allowing easy collaboration, updating, data sourcing and flexible analyses. With support from major institutions, this pipeline should be re‐run at regular intervals, storing trees and their metadata long‐term. Providing the trees to a diverse global audience through user‐friendly front ends and application development interfaces should also be a priority. Interactive interfaces could be used to solicit user feedback and thus improve data quality and to coordinate the generation of new data. We conclude by outlining a number of steps that we suggest the scientific community should take to achieve global phylogenetic synthesis.